2022
DOI: 10.1002/jor.25270
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative angiography imaging correlates with wound complications following soft tissue sarcoma resection

Abstract: For soft tissue sarcoma patients receiving preoperative radiation therapy, wound complications are common and potentially devastating. The purpose of this study was to assess the feasibility of intraoperative indocyanine green fluorescent angiography (ICGA) as a predictor of wound complications in these patients. A consecutive series of patients with soft tissue sarcoma of the extremities or pelvis who received neoadjuvant radiation and a subsequent radical resection received intraoperative ICGA with the SPY P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A prospective trial of transcutaneous oximetry was found to not reliably predict wound healing complications in STS 88 . Intraoperatively, laser angiography has been used with some preliminary positive results for its use in predicting wound healing, 89 while prophylactic antibiotics were associated with reduced major wound complications when including anaerobic coverage 90 . Postoperatively, recent publications 91 and current trials (NCT04960332 and NCT05944913) are currently exploring incisional NPWT.…”
Section: Radiation Therapymentioning
confidence: 99%
“…A prospective trial of transcutaneous oximetry was found to not reliably predict wound healing complications in STS 88 . Intraoperatively, laser angiography has been used with some preliminary positive results for its use in predicting wound healing, 89 while prophylactic antibiotics were associated with reduced major wound complications when including anaerobic coverage 90 . Postoperatively, recent publications 91 and current trials (NCT04960332 and NCT05944913) are currently exploring incisional NPWT.…”
Section: Radiation Therapymentioning
confidence: 99%